Experimental and SPH study of cold spray impact between similar and dissimilar metals. (June 2014) - Manap, A.; Nooririnah, O.; Misran, H.; Okabe, T.; Ogawa, K.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the critical, maximum and optimum velocity of a single cold sprayed (CS) particle is estimated using the smoothed particle hydrodynamics (SPH) method by evaluating the impact shape coefficient of restitution, as well as the rebound and deposit energy ratio. The contact surfaces of the particle and the substrate are modelled as intersurface forces using the Dugdale–Barenblatt cohesive zone model. The application of SPH allows the simulation of the CS process without the use of mesh, thereby avoiding the disadvantages of the traditional numerical method in handling large deformations and tracing moving interfaces. The impact of CS particles is simulated using various powder and substrate materials. The influence of the materials on the optimum velocity and the coating quality is discussed. The reliability of the model is verified with CS experiments.